Stimuli-responsive Drug Delivery Systems as an Emerging Platform for Treatment of Rheumatoid Arthritis - Xu, Xiao-Ling; Lu, Kong-Jun; Yao, Xiao-Qin; Ying, Xiao-Ying; Du, Yong-Zhong (Current Pharmaceutical Design, 2019)
Rheumatoid Arthritis (RA) is a systemic autoimmune disease accompanied by chronic inflammation. Due to the long-term infiltration in inflammatory sites, joints get steadily deteriorated, eventually resulting in functional incapacitation and disability. Despite the considerable effect, RA sufferers treated with current drug therapeutic efficacy are exposed to severe side effects. Application of Drug Delivery Systems (DDS) has improved these situations while the problem of limited drug exposure remains untackled. Stimuli-responsive DDS that are responsive to a variety of endogenous and exogenous stimuli, such as pH, redox status, and temperature, have emerged as a promising therapeutic strategy to optimize the drug release. Herein, we discussed the therapeutic regimes and serious side effects of current RA therapy, as well as focused on some of the potential stimuliresponsive DDS utilized in RA therapy. Besides, the prospective room in designing DDS for RA treatment has also been discussed.
Keywords: therapeutic approaches